Environmental Geotechnology Proceedings of EGRWSE 2018 - Agnihotri, Arvind Kumar; Reddy, Krishna R.; Bansal, Ajay.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains selected papers presented during the International Conference on Environmental Geotechnology, Recycled Waste Material and Sustainable Engineering (EGRWSE-2018). The multidisciplinary articles included in this volume cover the fields of environmental management, site characterization, environmental risk assessment, waste disposal, soil and groundwater remediation, habitat protection, and environmental rehabilitation. This volume will be of interest to professionals and researchers working in diverse fields ranging from geotechnical engineering, environmental engineering, hydrogeology, earth science, geochemistry, water engineering, and ecology, among others.
Role of Geochemistry in Sustainable Geotechnics -- Development on the Technology for Offshore Waste Final Disposal in S. Korea -- Quantitative X-Ray Diffraction Technique for Waste Beneficial Use Opportunities -- Sustainable Soil Remediation Phytoremediation Amended with Electric Current -- Environmental Impact of Mine Wastes: An Overview of Problems with Mining Sites in Turkey, Remediation Possibilities, and An Example from Turkey -- From Black Liquor to Green Material: Enzymatic Valorization of Pulp Industry by-Products -- Effect of Zinc Contamination on Engineering Properties of Clayey Soils -- Minimization of Biosludge from Tannery Effluent Using Anoxic Modified Conventional Activated Sludge Process -- Understanding Speciation and Leaching of Heavy Metals from a Polluted Site, Surat, Gujarat -- Model study of piled raft foundation -- Effective Utilization of Construction & Demolition Waste, Pond Ash in Combination with Geosynthetics in Flexible Road Pavement -- Utilization of Municipal Solid Waste Ash for Stabilization of Cohesive Soil.
Keywords: Engineering geology; Environmental engineering; Biotechnology; Bioremediation; Geotechnical engineering; Geoengineering; Environmental Engineering/Biotechnology.; Geotechnical Engineering and Applied Earth Sciences